The role of cGAS in epithelial dysregulation in inflammatory bowel disease and gastrointestinal malignancies - Ramos, Anna; Bizri, Nazih; Novak, Elizabeth; Mollen, Kevin; Khan, Sidrah (Frontiers in Pharmacology, 2024)
The gastrointestinal tract is lined by an epithelial monolayer responsible for selective permeability and absorption, as well as protection against harmful luminal contents. Recognition of foreign or aberrant DNA within these epithelial cells is, in part, regulated by pattern recognition receptors such as cyclic GMP-AMP synthase (cGAS). cGAS binds double-stranded DNA from exogenous and endogenous sources, resulting in the activation of stimulator of interferon genes (STING) and a type 1 interferon response. cGAS is also implicated in noncanonical pathways involving the suppression of DNA repair and the upregulation of autophagy via interactions with PARP1 and Beclin-1, respectively. The importance of cGAS activation in the development and progression of inflammatory bowel disease and gastrointestinal cancers has been and continues to be explored. This review delves into the intricacies of the complex role of cGAS in intestinal epithelial inflammation and gastrointestinal malignancies, as well as recent therapeutic advances targeting cGAS pathways.